2014
DOI: 10.1152/ajpregu.00193.2014
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin-28 inhibitory action on somatolactin-α and -β gene expression in goldfish

Abstract: Somatostain (SS) is known to inhibit growth hormone (GH) and prolactin (PRL) secretion. Somatolactin (SL) is a member of the GH/PRL family, but its regulation by goldfish brain somatostatin-28 (gbSS-28) has not been examined. To this end, the structural identity of goldfish SLα was established by 5'/3'-rapid amplification of cDNA ends. As revealed by in situ hybridization and immunohistochemical staining, the expression of SL isoforms was detected in pituitary cells located in the neurointermediate lobe (NIL).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…For examples, stimulatory effects of IGF-I on prolactin (PRL) secretion and gene expression has been reported in hybrid striped bass [46] while similar stimulation on LH and FSH secretion has also been observed in salmon [47] and European eel [48] pituitary cell cultures. In cyprinid species, somatolactin expression at the pituitary level, including SLα and SLβ, is under the control of hypothalamic factors, including PACAP [49,50] and somatostatin [51], as well as endocrine signals from peripheral tissues, e.g., IGF-I and -II [19]. More recently, a novel autocrine/paracrine component with SLα- and SLβ-induced SLα secretion and gene expression have been demonstrated in grass carp pituitary cells [52], suggesting the presence of somatolactin autoregulation occurring at the pituitary level.…”
Section: Discussionmentioning
confidence: 99%
“…For examples, stimulatory effects of IGF-I on prolactin (PRL) secretion and gene expression has been reported in hybrid striped bass [46] while similar stimulation on LH and FSH secretion has also been observed in salmon [47] and European eel [48] pituitary cell cultures. In cyprinid species, somatolactin expression at the pituitary level, including SLα and SLβ, is under the control of hypothalamic factors, including PACAP [49,50] and somatostatin [51], as well as endocrine signals from peripheral tissues, e.g., IGF-I and -II [19]. More recently, a novel autocrine/paracrine component with SLα- and SLβ-induced SLα secretion and gene expression have been demonstrated in grass carp pituitary cells [52], suggesting the presence of somatolactin autoregulation occurring at the pituitary level.…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, β-actin was used as an internal control for normalizing genes of interest. It has been reported that β-actin is used to normalize SL gene expression in tilapia ( 14 ), goldfish ( 32 ), and red drum ( 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…The duration of the GCGb treatment was fixed at 30 min. After that, cAMP production was quantified using a cAMP ELISA kit (EIAab Science Co., Ltd, Wuhan, China) as previously described ( 32 ). The assay for cAMP had a detection sensitivity range of 40–2,500 pmol/L.…”
Section: Methodsmentioning
confidence: 99%